2021
DOI: 10.1177/0013161x211003134
|View full text |Cite
|
Sign up to set email alerts
|

Linking Student Outcomes to School Administrator Discretion in the Implementation of Teacher Observations

Abstract: Purpose: Many studies have explored school administrator discretion in the implementation of teacher evaluation and observation systems. However, we are unaware of any studies that quantitatively link discretionary administrator behaviors to student outcomes. The purpose of this study was to (a) explore the determinants of observations arising from administrator discretion and (b) explore the extent to which “discretionary observations” were associated with average student achievement scores and disciplinary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…1 A growing body of work suggests that the success of these reforms rests partly on teacher observation processes and the policies that shape them (Donaldson, 2021). Specifically, teaching improvements seem to depend on the quality of observers’ training (Steinberg & Sartain, 2015), observers’ discretion in the implementation of teacher observations, structured observation conferences, or post-observation improvement plans (Donaldson & Woulfin, 2018; Hunter & Ege, 2021; Marsh et al, 2017), and teachers’ receipt of observations (Phipps, 2018; Phipps & Wiseman, 2021). Recent quasi-experimental work also indirectly implies that observations improve teachers’ performance by increasing their motivation via accountability mechanisms and performance feedback (Phipps & Wiseman, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…1 A growing body of work suggests that the success of these reforms rests partly on teacher observation processes and the policies that shape them (Donaldson, 2021). Specifically, teaching improvements seem to depend on the quality of observers’ training (Steinberg & Sartain, 2015), observers’ discretion in the implementation of teacher observations, structured observation conferences, or post-observation improvement plans (Donaldson & Woulfin, 2018; Hunter & Ege, 2021; Marsh et al, 2017), and teachers’ receipt of observations (Phipps, 2018; Phipps & Wiseman, 2021). Recent quasi-experimental work also indirectly implies that observations improve teachers’ performance by increasing their motivation via accountability mechanisms and performance feedback (Phipps & Wiseman, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although a previous study concluded that school administrators deliver higher dosages of effective feedback to historically less effective early-career teachers (Hunter and Springer, 2022), findings from the current study and other prior research suggest the opposite. For example, Hunter and Ege (2021) studied school administrator implementation of teacher observation processes in a setting where highly effective teachers are assigned one or two observations, and the least effective teachers are assigned four. In that study, school administrators visited the classrooms of teachers needing the least improvement (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, school administrators visited the classrooms of teachers needing the least improvement (i.e. historically highly effective teachers) more than the number of times assigned by policy (Hunter and Ege, 2021). The current study also finds that administrators implement observations in ways that may not improve teaching among those needing it the most by providing historically less effective teachers with less well-implemented observations [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations